Analysis and Profiling of Agri-Entrepreneurship Promoting Institutions (Indian Journal of Extension Education, 2024)
The agricultural sector is undergoing a shift from subsistence-based practices to a business oriented approach. Recognizing the importance of promoting agripreneurs, numerous organizations are actively engaged in fostering agri-entrepreneurship. An in-depth institutional profile analysis was conducted on sixteen agri-entrepreneurship promoting institutions in the states of Rajasthan and Telangana during 2022-23. Data were gathered from professionals within these organizations. The analysis focused on 12 key parameters, employing an exploratory research design, and utilizing empirical evidence for data collection. Correspondence Analysis was carried out to assess 15 strategic areas based on their significance. The strategic areas receiving the highest focus included branding and PR, help during pitching, certification, providing co-working spaces, and training. Conversely, intellectual property management and funding received comparatively less emphasis. These findings provide valuable insights into the key areas of support prioritized by agri-entrepreneurship promoting institutions.